2014
DOI: 10.1259/bjr.20140003
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of spinal osteoid osteoma under CT guidance

Abstract: Objective: Osteoid osteoma (OO) accounts for approximately 10-12% of all benign bone tumours and 3% of all bone tumours. Spinal involvement appears in 10-25% of all cases. The purpose of this study was to evaluate the safety and efficacy of CT-guided radiofrequency (RF) ablation in the treatment of spinal OOs and report our experience. Methods: 13 patients suffering from spinal OO and treated at the authors' institution using CT-guided RF ablation were retrospectively evaluated. The RF probe was introduced thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
(30 reference statements)
0
15
1
Order By: Relevance
“…They may be the first choice if the lesion location is appropriate. Small series with good clinical results are increasing in literature in last decade (17,19,(46)(47)(48). However, there are some drawbacks for these treatment types.…”
Section: Treatmentmentioning
confidence: 99%
“…They may be the first choice if the lesion location is appropriate. Small series with good clinical results are increasing in literature in last decade (17,19,(46)(47)(48). However, there are some drawbacks for these treatment types.…”
Section: Treatmentmentioning
confidence: 99%
“…[28][29][30][31] Previous research has confirmed the protective nature of cortical bone between the RFA probe and adjacent soft tissues 27,32 and that there is limited transfer of heat to the vertebral canal. 33 Although thermoprotective measures in the spine have been described, 34 there is no in vivo (or in vitro) evidence that these do in fact serve to provide additional protection for neural structures.…”
Section: Discussionmentioning
confidence: 99%
“…Morassi et al reported VAS decrease from 8.6 to 0 for their 11 patients after the procedure. Two of patients were considered as recurrence and after second procedure their VAS reduced to 0 as well [ 23 ]. In our study VAS reduction for both day and nighttime was statistically significant.…”
Section: Discussionmentioning
confidence: 99%